Perkembangan Psikologi Anak dalam Pendidikan Karakter di Sekolah Dasar Negeri 157 Palembang - Astuti, Mardiah; Putri Pratiwi, Zakiah; Iklimah, Leyin; Septiani, Lisa; Karunia, Tria; Mutyati; Ibrahim (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The article explores the advancement of character education in psychology for sixth-grade students at SD Negeri 157 Palembang. The research employs qualitative techniques encompassing interviews, observations, and document analysis. The findings from this approach indicate the typical character traits. the students in the class vary. However, overall, sixth-grade students tend to have religious, disciplined, and cooperative characters. The understanding of the school principal, religion teachers, and parents regarding the development of children's psychology in character education has received a positive response. Collaboration and open communication between the school and parents are crucial for the child's psychological development in character education. The head of the school enforces the school's vision and mission aiming to cultivate students characterized by religiosity, discipline, honesty, and compassion for others. Based on the aforementioned results and analysis, it can be inferred that the advancement of child psychology in character development at SD Negeri 157 Palembang, particularly for sixth-grade students, manifests positive growth. This is evident from the interviews conducted with the school principal, class teachers, and religious educators